Making a Case for Creating Living Labs for Aging-in-Place: Enabling Socially Innovative Models for Experimentation and Complementary Economies - Spinelli, Gabriella; Weaver, Paul; Marks, Michael; Victor, Christina (Frontiers in Sociology, 2019)
Ageing is continuously depicted as a force majeure event despite clear and robust premonitions of its coming. However, such depiction serves to justify the unpreparedness and inadequacy of policies manifesting in loneliness and isolation, unsatisfied demands in health and social care, lack of suitably inclusive residential and social facilities, and inequitable access to support and services. Recent years have seen an increase in social innovation that involves alternative transaction models, such as time-banks and circular economies. These initiatives represent collective responses to changes and challenges such as ageing by identifying and innovatively capturing and exchanging locally- and freely- available assets with the intent to fulfil economic needs (more affordable goods and services), social ambitions (skills development and exchange, repurposing space, social inclusion and cohesion) environmental aspirations (up-cycle) and psychological needs (sense of purpose, identity, belonging, recognition). Whilst it is often assumed that ad hoc measures are appropriate to resolve the challenges posed by an ageing demographic, the learnt assumption that underpins this work is that ageing is a systemic issue and ought to be understood, and resolved, in its context, not by producing niche- relevant policy and interventions, but considering the impacts it has on the whole society. Henceforth it is proposed that truly transformative social innovation for the ageing population must consider and resolve the challenges of communities as there is where older adults can stay relevant socially and, in the presented approach, also economically. Through the review of four international case studies a framework with four cornerstones has emerged. This includes the changing role of local and central governments, the models of value creation, co-creation mechanisms and, finally, technology, especially digital social currency. The concurrent presence of the four factors in the framework is not always a requirement for social innovation to emerge and flourish. However, the presented analysis suggests that all four themes have an impact even when not being direct agents of social innovation. The authors conclude by making a case for developing Living Labs for Ageing in Place, to experiment and study proposed solutions for systemic challenges facing the ageing population, grounded in community-led schemes.